2013
DOI: 10.1088/0004-637x/778/1/43
|View full text |Cite
|
Sign up to set email alerts
|

Global Numerical Modeling of Energetic Proton Acceleration in a Coronal Mass Ejection Traveling Through the Solar Corona

Abstract: The acceleration of protons and electrons to high (sometimes GeV/nucleon) energies by solar phenomena is a key component of space weather. These solar energetic particle (SEP) events can damage spacecraft and communications, as well as present radiation hazards to humans. In-depth particle acceleration simulations have been performed for idealized magnetic fields for diffusive acceleration and particle propagation, and at the same time the quality of MHD simulations of coronal mass ejections (CMEs) has improve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 60 publications
0
79
0
Order By: Relevance
“…This is essential to find the correct solution of DSA. The shock thickness resolved in this study is much less than the cell size of MHD simulations that include the calculation of particle acceleration in a similar way (e.g., Kozarev et al 2013;Schwadron et al 2015).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is essential to find the correct solution of DSA. The shock thickness resolved in this study is much less than the cell size of MHD simulations that include the calculation of particle acceleration in a similar way (e.g., Kozarev et al 2013;Schwadron et al 2015).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In particular, as mentioned earlier, compelling observational evidence exists for the shock formation and particle acceleration close to the Sun. Therefore, modeling shock acceleration in the low corona is of great importance for understanding the underlying mechanisms for producing large SEP events (e.g., Berezhko & Taneev 2003Kocharov et al 2005;Vainio & Laitinen 2007;Ng & Reames 2008;Sandroos & Vainio 2009a, 2009bKozarev et al 2013;Schwadron et al 2015). Ng & Reames (2008) modeled particle acceleration at a parallel shock with a speed of 2500 km s −1 starting at 3.5 R e and showed that particles can be accelerated to >300 MeV in 10 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond its use for characterization of CBFs, it can be important for the SEP acceleration process. As shown in multiple studies (Manchester et al, 2005;Giacalone & Kóta, 2006;Kozarev et al, 2013;Schwadron et al, 2015), SEPs may be accelerated also in the pile-up region behind shocks or in compressive waves that do not exhibit the step-like plasma change characteristic of shocks provided the particles possess enough energy.…”
Section: This Methods Is Illustrated Inmentioning
confidence: 98%
“…Detailed simulations of particle acceleration in realistically modeled CMEs near the Sun show that shocks form very early and can accelerate protons to hundreds of MeV (Sokolov et al, 2009;Kozarev et al, 2013). However, due to the lack of in situ measurements of particles and fields in the corona, our understanding of the acceleration and transport processes there is quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors, like different seed particle populations (e.g., Li & Zank 2005;Tylka et al 2005;Battarbee et al 2011;Vainio et al 2014) or the inclusion of a variable magnetic field (i.e. non-Parker morphology of the IMF) as studied by different authors (e.g., Giacalone 2005;Kocharov et al 2009;Guo et al 2010;Kozarev et al 2013), have not been included in SaP yet. Our next step, together with the improvement of the modelling of the foreshock region as commented on in the previous section, is to study the correlation between Q and other parameters, particularly with h Bn , in order to, eventually, find a multi-parameter dependence of Q.…”
Section: Discussionmentioning
confidence: 99%